2020
DOI: 10.3390/microorganisms8091449
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics between Erwinia amylovora, Pantoea agglomerans and Bacteriophages: Exploiting Synergy and Competition to Improve Phage Cocktail Efficacy

Abstract: Bacteriophages are viruses capable of recognizing with high specificity, propagating inside of, and destroying their bacterial hosts. The phage lytic life cycle makes phages attractive as tools to selectively kill pathogenic bacteria with minimal impact on the surrounding microbiome. To effectively harness the potential of phages in therapy, it is critical to understand the phage–host dynamics and how these interactions can change in complex populations. Our model examined the interactions between the plant pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…With Ea6-4 confirmed to have CRISPR-Cas activity through plasmid transformation, CRISPR-Cas activity was tested using phage Kolesnikvirus Erwinia virus Ea214 (ΦEa21-4). ΦEa21-4 was first isolated on Ea6-4 and is a candidate for phage biocontrol of E. amylovora ( 26 30 ). To this end, characteristics about the lytic replication cycle (i.e., adsorption rate, burst size, and time to lysis) have been previously described on this bacterial host through quantitative, real-time PCR (qPCR) ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…With Ea6-4 confirmed to have CRISPR-Cas activity through plasmid transformation, CRISPR-Cas activity was tested using phage Kolesnikvirus Erwinia virus Ea214 (ΦEa21-4). ΦEa21-4 was first isolated on Ea6-4 and is a candidate for phage biocontrol of E. amylovora ( 26 30 ). To this end, characteristics about the lytic replication cycle (i.e., adsorption rate, burst size, and time to lysis) have been previously described on this bacterial host through quantitative, real-time PCR (qPCR) ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…This study presents the classification of bacterial growth dynamics in the presence of lytic phages using two statistical data mining techniques: NMDS and PCA. OD as the input is a fast and data-rich screening method for in vitro phage-host growth dynamics [35]. This approach captures the ongoing dynamics and produces a quantitative high-throughput data to determine the phage-host range, phage virulence/infectivity, and bacterial phage resistance development [16,32,36].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the emergence of phage resistance, we should prioritize the use of phage mixtures [ 96 ] when using PT. Gayder found that competition and synergy between bacteriophages can be used to enhance the antibacterial efficacy of bacteriophage mixtures [ 97 ]. We should take advantage of the interactions between bacteriophages and bacteria to improve our battle against bacteria.…”
Section: Solutions To the Limitations Of Ptmentioning
confidence: 99%